NILAI-NILAI PENDIDIKAN ISLAM DALAM HADIS-HADIS AKIKAH - Nurul Azizah (Universitas Wahid Hasyim Semarang, 2019)
AbstracAkikah is a form of parental love and the provision of the first education for children. The marriage practiced by the Jahiliyah in ancient times was replaced by the Prophet with the practices of Islamic marriage andcontained educational value in it. This study focused on the akikah traditionscontained in the book of hadith mu'tabar. This research is a qualitativeresearch in the form of a research library that collects data from relevantbooks. The purpose of this study is to find out the akikah rituals contained inthe hadith of marriage, and to know the value of Islamic education containedin it.This research shows that the akikah hadith narrated by Abi Buraidah,Ali, Samurah, and 'Aisyah contain several rituals, including: cutting a child'shair, smearing his hair with za'faran oil, alms as heavy as hair that has beencut, named, tahnik, and akikah. From this practice, akikah contains values ofIslamic education, including: faith education, moral education, healtheducation, social education, psychology education, and beauty education.Key Word: Islamic Education, Hadits AkikahAbstrakAkikah merupakan bentuk kasih sayang orang tua dan pemberianpendidikan pertama bagi anak. Akikah yang dipraktekkan orang Jahiliyahpada zaman dahulu diganti oleh Rasulullah dengan praktik-praktik akikahislami dan mengandung nilai pendidikan di dalamnya. Penelitian inidifokuskan pada hadis-hadis akikah yang terdapat dalam kitab hadismu’tabar. Penelitian ini merupakan penelitian kualitatif berupalibraryresearchyang mengumpulkan data-data dari buku-buku yang relevan.Tujuan penelitian ini untuk mengetahui ritual-ritual akikah yang terdapatdalam hadis akikah, serta untuk mengetahui nilai pendidikan Islam yangterdapat di dalamnya. Penelitian ini menunjukkan bahwa hadis akikah yang diriwayatkan oleh Abi Buraidah, Ali, Samurah, dan ‘Aisyah mengandung beberapa ritual, di antaranya: memotong rambut anak, melumuri rambutnyadengan minyak za’faran, sedekah seberat rambut yang telah dipotong, diberinama, tahnik, dan akikah. Dari praktik tersebut, akikah mengandung nilai-nilai pendidikan Islam, di antaranya: pendidikan keimanan, pendidikan akhlak, pendidikan kesehatan, pendidikan sosial, pendidikan psikologi, dan pendidikan keindahan.Kata Kunci: Pendidikan Islam, Hadis Akikah.